2017
DOI: 10.3390/w9110874
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Use of Water Resources in the Steel Industry

Abstract: Abstract:In the steel sector water management aims at improving the sustainability of the production cycle, resulting in resource efficiency benefits and in reduced water demand and costs. To be reused, water needs to be cooled and desalinized to avoid salt concentration in water circulation systems. The presented work includes two case studies carried out in an integrated steelmaking plant, respectively, to evaluate the possible implementation of ultrafiltration and reverse osmosis to reduce salt concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Our results indicate that students in this study formed notable opinions about these topics. Participants in industrial sectors also reported that the topics were similar to real-world issues, such as choosing between producing goods to earn money, saving water, or developing technology for WRA [47]. Moreover, the students who played the public guild noted that their main responsibility was to maximize public benefits [13].…”
Section: Issue Situations For Opinions On Forming Rolesmentioning
confidence: 99%
“…Our results indicate that students in this study formed notable opinions about these topics. Participants in industrial sectors also reported that the topics were similar to real-world issues, such as choosing between producing goods to earn money, saving water, or developing technology for WRA [47]. Moreover, the students who played the public guild noted that their main responsibility was to maximize public benefits [13].…”
Section: Issue Situations For Opinions On Forming Rolesmentioning
confidence: 99%
“…The average water intake for an integrated steelworks is 28.6 m 3 per tonne of produced steel, with an average water discharge of 25.3 m 3 /tonne of steel. For the electric route, the average intake is 28.1 m 3 per tonne of steel, with an average discharge of 26.5 m 3 per tonne of steel (Colla et al, 2017). Mt (Schorcht et al, 2013).…”
Section: Wa S Te Water -An Indus Trial Re Sourcementioning
confidence: 99%
“…The efficiency of industrial water use is measured mainly by economic benefits. This sector includes many relevant indicators such as industrial water recycling rate, unilateral water industrial output value, industrial water quota, ten thousand Yuan added value water withdrawal, process water reuse rate, and industrial water supply guarantee the compliance rate [24]. In view of the ongoing economic transformation in the Beijing-Tianjin-Hebei region, as the service industry is an important pillar of economic development, the water efficiency of this sector should by no means be ignored.…”
Section: Economic Subsystemmentioning
confidence: 99%